Tren Virtual Hotel Operator (VHO) di Yogyakarta: Studi Kasus Hotel Oyo - Fitri Kusumawati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
This study aims to look at the trends of the OYO Hotel in Yogyakarta. This research is qualitative research with a case study research design. Data collection techniques used were observation, interviews, and literature review. Whereas data analysis uses an interactive analysis model. The results showed that the trend of OYO hotels is increasingly developing in Yogyakarta in line with the trend of travelling with a minimal budget. factors affecting tourists in choosing OYO are: cheap room rates, the number of room promotions, quality and service according to standards, adequate facilities, ease of application-based reservations, and payment can be done at the hotel